Children's activities, parental concerns, and child care service utilization in the early stages of the COVID-19 pandemic - Zhang, Jasmine; Smith, Jackson; Browne, Dillon (Frontiers in Public Health, 2023)
In the early stages of the COVID-19 pandemic, most Canadian provinces and territories enacted public health measures to reduce virus spread, leading most child care centers across the country to limit or halt in-person service delivery. While it is broadly known that the range of activities available to children and youth reduced drastically as a result, research has yet to explore if and how children’s activities shifted in relation to changes in child care arrangements. To address this knowledge gap, children’s activities during the early months of the pandemic were assessed based on parent-report data (N = 32,228). Latent profile analysis yielded three distinct activity patterns: Screenies (91.5%) were children who engaged in high amounts of screen use relative to all other activities; Analog children (3.1%) exhibited mostly off-screen activities (e.g., reading, physical exercise); and children in the Balanced group (5.4%) appeared to pursue a wide variety of activities. Logistic regression models revealed that children were more likely to fall into the Screenies or Balanced profiles when caregivers reported changes in child care arrangements. Moreover, parents of children with Balanced activity profiles were more likely to be planning to use child care when services reopened post-pandemic, compared to parents of children in the Analog group. The present findings call attention to heterogeneity in children’s activities during COVID-19, which should be considered in the context of pandemic-related child care closures. Implications for children, families, and child care services during and beyond COVID-19 are discussed.